HARMONIZING PEDAGOGY AND MANAGEMENT: AN INTEGRATED SONG-BASED MODEL FOR EARLY LITERACY IN A MULTILINGUAL CONTEXT - Dorce Butu; Krislina Pattipeiluhu; Riski Tasijawa (Sanata Dharma University Yogyakarta, 2026)
This study examines the issue of low proficiency in Indonesian among young children in Sentani, which is attributed to the dominance of local dialects and low self-confidence among the children. The primary objective of this study is to identify gaps in school operational management that are often overlooked in research on language literacy in early childhood. Specifically, this study analyses the strategic role of teachers as facilitators, language models, and motivators in song-based learning, as well as identifying managerial factors that support literacy success in multilingual areas. This qualitative study, which employs a single-case study design, was conducted at the Alethea Sentani Early Childhood Education Centre. Research participants included the headteacher, teachers, and pupils selected through purposive sampling. Data were collected through participant observation, in-depth interviews, and document analysis, and were subsequently analysed interactively using the model proposed by Miles, Huberman, and Saldaña, with verification through member checking. The research findings indicate that the success of language development is largely determined by the optimisation of teachers’ managerial roles and institutional support. This study validates the Integrated Song-Based Language Learning Management Model (ISBLLM) as a harmonious ecosystem that integrates pedagogical and managerial aspects to address literacy barriers in remote and multilingual areas.